Particulate compositions comprising metal precursors for additive manufacturing and related methods

By using a particulate composition of thermoplastic polymer and laser-activated metal precursor in the additive manufacturing process, the problem of inaccurate placement of conductive traces in the prior art is solved, and the problem of inaccurate placement of conductive traces is achieved Efficient and accurate conductive trace formation.

CN112454890BActive Publication Date: 2025-02-14XEROX CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010876583.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2020-08-27
Publication Date
2025-02-14
Estimated Expiration
2040-08-27

AI Technical Summary

Technical Problem

It is difficult for existing additive manufacturing processes to directly introduce conductive traces during component manufacturing, resulting in inaccurate placement of conductive traces and cumbersome process.

Method used

Using a particle composition containing a thermoplastic polymer and a metal precursor activated by laser irradiation, discontinuous metal islands are formed during the additive manufacturing process by selective laser sintering process, thereby forming conductive traces on the surface of the printed object. .

Benefits of technology

The direct formation of conductive traces in the additive manufacturing process is achieved, which improves the placement accuracy and manufacturing efficiency of conductive traces, and avoids the cumbersome process of inkjet printing or aerosol jetting technology alone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112454890B_ABST
    Figure CN112454890B_ABST
Patent Text Reader

Abstract

The present invention is entitled "Particulate compositions containing metal precursors for additive manufacturing and related methods thereof". Additive manufacturing processes, such as powder bed fusion of thermoplastic particles, can be used to form printed objects of a range of shapes. Sometimes it is desirable to form conductive traces on the surface of the printed object. Conductive traces and similar features can be introduced during the additive manufacturing process by incorporating a metal precursor into a thermoplastic printing composition, converting a portion of the metal precursor into discontinuous metal islands using laser irradiation, and performing electroless plating. A suitable printing composition can include a plurality of thermoplastic particles, the plurality of thermoplastic particles comprising a thermoplastic polymer, a metal precursor blended with the thermoplastic polymer, and optionally a plurality of nanoparticles disposed on the outer surface of each thermoplastic particle in the thermoplastic particles, wherein the metal precursor is capable of being activated to form metal islands when exposed to laser irradiation. Melt emulsification can be used to form the thermoplastic particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates generally to additive manufacturing, and more particularly to additive manufacturing processes that employ powder bed fusion (PBF), such as those that employ selective laser sintering to produce complex objects and particulate compositions for use in the complex objects, wherein metal precursors that are activatable by laser irradiation (such as laser irradiation delivered from a pulsed laser) are incorporated during the printing process. Background Art

[0002] Additive manufacturing, also known as three-dimensional (3D) printing, is a rapidly growing field of technology. Although additive manufacturing has traditionally been used for rapid prototyping activities, the technology is increasingly being used to produce commercial and industrial parts (printed objects) with any number of complex shapes. The additive manufacturing process operates by depositing layer by layer either of the following substances: 1) a stream of molten printing material or a liquid precursor of the printing material, or 2) powder particles of the printing material. The layer-by-layer deposition is typically performed under computer control to deposit and consolidate the printing material at precise locations based on a digital three-dimensional "blueprint" (computer-aided design model) of the part to be manufactured. In a specific example, the consolidation of the powder particles can be performed in a powder bed deposited layer by layer using a three-dimensional printing system that uses a laser or electron beam to heat the precise location of the powder bed, thereby consolidating specific powder particles to form a part with a desired shape. The melting of the powder particles in the powder bed can be performed by selective laser sintering (SLS), which uses a laser to promote the consolidation of the powder particles via local heating.

[0003] Among these powder particles, those that are useful for 3D printing are those that contain thermoplastic polymers. Although a wide range of thermoplastic polymers are known, relatively few have compatible properties for use with current 3D printing techniques, particularly when particle consolidation is performed by selective laser sintering. Thermoplastic polymers suitable for consolidation by selective laser sintering include those that have a significant difference between the onset of melting and the onset of crystallization that promotes good structural and mechanical integrity.

[0004] In some cases, it may be desirable to form conductive traces on the surface of an additively manufactured part. Currently, such conductive traces are formed by a separate inkjet printing, aerosol jet or direct writing process to deposit ink infused with a conductive material (such as graphite or metal) on the surface of the part, which is then cured or sintered to facilitate the formation of a conductive path. The deposition of such conductive inks occurs under conditions that are completely different from the additive manufacturing process, requiring the printed parts to be transferred between production lines. In many cases, the process can be cumbersome and time-consuming, especially when extreme accuracy is required to place the conductive traces. When conductive traces are formed in this manner, accurate placement of the conductive traces on curved (non-flat) surfaces of the printed object can be particularly problematic. Additional difficulties may arise due to poor adhesion between certain thermoplastic polymers and the conductive inks used in conjunction with inkjet printing processes and aerosol jet printing processes. Summary of the invention

[0005] The present disclosure provides particulate compositions suitable for additive manufacturing. The particulate compositions include: a plurality of thermoplastic particles, the plurality of thermoplastic particles including a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation. Optionally, the thermoplastic particles may include a plurality of nanoparticles disposed on an outer surface of each thermoplastic particle in the plurality of thermoplastic particles.

[0006] The present disclosure also provides a printed object formed using the microparticle composition. The printed object comprises: a polymer matrix formed by consolidation of microparticles and comprising a thermoplastic polymer; and a metal precursor blended with the polymer matrix, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation. Optionally, a plurality of nanoparticles may be blended with the polymer matrix in the printed object.

[0007] The present disclosure also provides a method for forming a printed object by powder bed fusion (such as by selective laser sintering). The method includes: depositing a particulate composition in a powder bed, the particulate composition comprising a plurality of thermoplastic particles, the plurality of thermoplastic particles comprising a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation; and consolidating a portion of the plurality of thermoplastic particles in the powder bed to form a printed object, in which the metal precursor remains substantially unconverted to metal. Optionally, the plurality of thermoplastic particles further comprises a plurality of nanoparticles, the plurality of nanoparticles being disposed on an outer surface of each of the plurality of thermoplastic particles.

[0008] The present disclosure also provides a method for forming a particulate composition suitable for additive manufacturing. The method includes: mixing a thermoplastic polymer with a metal precursor in a carrier fluid at a heated temperature at or above the melting point or softening temperature of the thermoplastic polymer; wherein the thermoplastic polymer and the carrier fluid are substantially immiscible at the heated temperature, and the metal precursor is capable of being activated to form metal islands when exposed to laser irradiation; applying sufficient shear at the heated temperature in the presence of the metal precursor to disperse the thermoplastic polymer as liquefied droplets; after the liquefied droplets are formed, the carrier fluid is cooled to at least a temperature to form thermoplastic particles in a solidified state, the thermoplastic particles comprising the thermoplastic polymer and at least a portion of the metal precursor blended with the thermoplastic polymer; and separating the thermoplastic particles from the carrier fluid. Optionally, nanoparticles may be mixed with the thermoplastic polymer and the metal precursor in the carrier fluid, such that at least a portion of the nanoparticles are disposed on the outer surface of each of the thermoplastic particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] The following drawings are included to illustrate certain aspects of the disclosure and should not be considered to be exclusive embodiments. The disclosed subject matter is capable of considerable modification, alteration, combination, and equivalents in form and function, as will occur to those of ordinary skill in the art having the benefit of this disclosure.

[0010] Figure 1 is a flow chart of a non-limiting example method for producing thermoplastic particulates according to the present disclosure.

[0011] Figure 2 is a diagram showing consolidation of thermoplastic particles by selective laser sintering to form a printed object followed by formation of metal islands using a pulsed laser. DETAILED DESCRIPTION

[0012] The present disclosure relates generally to additive manufacturing and, more particularly, to additive manufacturing methods that employ particulate consolidation (such as selective laser sintering and other powder bed fusion processes) for producing printed objects, wherein during the printing process a metal precursor is present that is capable of being activated by laser irradiation (such as provided by a pulsed laser), but the metal precursor remains substantially unactivated during the particulate consolidation.

[0013] As described above, additive manufacturing processes, such as those that employ selective laser sintering and other powder bed fusion processes to promote particulate consolidation, are capable of producing parts with a variety of complex shapes. Currently, it is not feasible to introduce conductive traces on the surface of printed parts as an integrated part of the additive manufacturing process. Instead, a separate aerosol, inkjet, or direct printing technique is used to deposit conductive ink on the surface of the printed object (part), followed by curing or sintering to promote conductivity. Separate printing techniques for depositing conductive inks can limit processing throughput and result in inaccurate placement of conductive traces. In some cases, there may also be poor adhesion between the thermoplastic polymer that makes up the printed object and the conductive ink used to deposit the conductive traces.

[0014] Advantageously, the present disclosure provides a way by which metal islands can be introduced during additive manufacturing processes (such as those using selective laser sintering and other powder bed fusion processes) without having to transfer the parts to a separate printing line after part manufacturing. Specifically, the present disclosure uses a particulate composition comprising a metal precursor that can be activated by laser irradiation, especially using a pulsed laser, to promote the formation of discontinuous metal islands on the surface of an object formed by additive manufacturing. Suitable metal precursors are non-conductive before activation and contain metals in a coordinated state and / or salt form. After activation, the metal precursor can be converted into a metal conductor. In some embodiments, the laser used to promote selective laser sintering can also be used to promote the formation of metal islands under processing conditions different from those used to perform particulate consolidation. Alternatively, a separate laser can be used to promote particulate consolidation and activate the metal precursor to form metal islands. That is, the process disclosed herein may employ two lasers: a first laser, such as a continuous laser, which is effective to promote the consolidation of powder particles but does not activate the metal precursor; and a second laser, such as a pulsed laser, which is effective to promote the formation of metal (metal islands) once the particle consolidation has been completed. It may be easy to incorporate a second laser within an apparatus for performing selective laser sintering and other powder bed fusion processes, thereby allowing the formation of metal islands without moving the printed object after the printed object is manufactured. Alternatively, the second laser for promoting the formation of metal islands may be in a different position from the first laser used for performing selective laser sintering. Since the position of the printed object remains fixed after manufacture and is known to have high accuracy during selective laser sintering and other powder bed fusion processes, metal islands can also be accurately placed on the printed object by using the disclosure herein. However, it should be understood that the second laser may alternatively be used in a separate system different from the system used to perform powder bed fusion for metal island formation.

[0015] Various metal precursors can be used in the disclosure of this article and are discussed in further detail below. Advantageously, such metal precursors can be easily incorporated into powder particles used in combination with selective laser sintering processes and other powder bed fusion processes. Such powder particles can be formed from thermoplastic polymers containing metal precursors, such as by conventional mechanical grinding or precipitation processes. However, it is more desirable that the metal precursors can be blended with thermoplastic polymers during a melt emulsification process (including those melt emulsification processes using extrusion processing of melt emulsions), which is used to form thermoplastic particles as powder compositions, as described in further detail herein. Particularly suitable melt emulsification processes can incorporate nanoparticles (such as carbon black and / or silica nanoparticles or other oxide nanoparticles) as emulsion stabilizers in the particle formation process, wherein the nanoparticles become disposed on the outer surface of the thermoplastic particles produced by the solidification of the liquefied thermoplastic polymer droplets. The coating or partial coating of the nanoparticles on the outer surface results in a narrow particle size distribution and high sphericity of the thermoplastic particles, which can provide good flow characteristics and easy particle consolidation during additive manufacturing. The metal precursor does not hinder the particle formation process, and the nanoparticles do not hinder the formation of metal islands after particle consolidation.

[0016] The terms used in this specification and claims have their plain and ordinary meanings except as modified in the following paragraphs.

[0017] As used herein, the term "immiscible" refers to a mixture of components that, when combined, form two or more phases that have less than 5 weight % solubility in each other at ambient pressure and room temperature or the melting points of the components if they are solid at room temperature. For example, polyethylene oxide having a molecular weight of 10,000 g / mol is solid at room temperature and has a melting point of 65° C. Thus, if a material that is liquid at room temperature and the polyethylene oxide have less than 5 weight % solubility in each other at 65° C., the polyethylene oxide is immiscible with the material.

[0018] As used herein, the term "thermoplastic polymer" refers to a polymer material that can reversibly soften and harden when heated and cooled. Thermoplastic polymers encompass thermoplastic elastomers.

[0019] As used herein, the term "nanoparticle" refers to particulate material having a particle size ranging from about 1 nm to about 500 nm.

[0020] As used herein, the term "oxide" refers to both metal oxides and non-metal oxides. For the purposes of this disclosure, silicon is considered a metal.

[0021] As used herein, the term "oxide nanoparticles" refers to particulate materials having a particle size ranging from about 1 nm to about 500 nm and comprising a metal oxide or a non-metal oxide.

[0022] As used herein, the term "associated" refers to chemical bonding or physical adhesion to a surface, particularly an emulsion stabilizer comprising nanoparticles. Without being limited by theory, it is believed that the association between the polymers described herein and the emulsion stabilizers is primarily physical adhesion via hydrogen bonding and / or other mechanisms. However, chemical bonding may occur to some extent.

[0023] As used herein, the term "incorporated" refers to the dissolution of a first substance in a second substance or the dispersion of a first substance as a solid in a second substance, wherein the dispersion may be uniform or non-uniform. In various embodiments, the metal precursor may be substantially uniformly dispersed throughout the interior of the thermoplastic particulate disclosed herein.

[0024] As used herein, the term "D10" refers to the diameter at which 10% of the sample (on a volume basis unless otherwise specified) consists of particles having a diameter less than the stated diameter value. As used herein, the term "D50" refers to the diameter at which 50% of the sample (on a volume basis unless otherwise specified) consists of particles having a diameter less than the stated diameter value. D50 may also be referred to as the "average particle size". As used herein, the term "D90" refers to the diameter at which 90% of the sample (on a volume basis unless otherwise specified) consists of particles having a diameter less than the stated diameter value.

[0025] As used herein, the term "shear" refers to stirring or similar processes that cause mechanical agitation in a fluid.

[0026] As used herein, the term "embedded" with respect to nanoparticles and polymer particle surfaces means that the nanoparticles extend at least partially into the surface such that the polymer contacts the nanoparticles to a greater extent than would occur if the nanoparticles were simply laid down on the polymer particle surface, thereby tangentially contacting the surface.

[0027] As used herein, unless otherwise indicated, the viscosity of a carrier fluid is the kinematic viscosity at 25°C and is measured according to ASTM D445-19 unless otherwise indicated.

[0028] Unless otherwise indicated, the melting point of thermoplastic polymers was determined by ASTM E794-06 (2018) with a 10°C / min ramp rate and cooling rate.

[0029] Unless otherwise indicated, the softening temperature or softening point of thermoplastic polymers is determined by ASTM D6090-17.The softening temperature can be measured using a cup and ball apparatus commercially available from Mettler-Toledo using a 0.50 gram sample at a heating rate of 1°C / min.

[0030] As used herein, the term "near infrared" region refers to the wavelength range of about 700 nm to about 1400 nm, which region is sometimes referred to as the IR-A region (as defined by the International Commission on Illumination).

[0031] The particulate composition of the present disclosure comprises thermoplastic particles and can be suitable for additive manufacturing processes, particularly additive manufacturing processes that use selective laser sintering to promote particle consolidation and pulsed lasers to promote the formation of metals from metal precursors. The particulate composition suitable for additive manufacturing can exhibit good flow characteristics so that it can be distributed in a powder bed using a print head or similar equipment. Flow aids and modifications to the thermoplastic particles can facilitate the distribution process. Suitable thermoplastic particles can also exhibit melting temperatures and crystallization temperatures that are compatible with specific consolidation techniques in a given additive manufacturing process. The particulate composition of the present disclosure suitable for additive manufacturing can include a plurality of particles, the plurality of particles comprising a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, wherein the metal precursor can be activated to form metal islands when exposed to laser irradiation, especially using a pulsed laser. More specific particulate compositions of the present disclosure suitable for additive manufacturing may include a plurality of particles comprising a thermoplastic polymer, a metal precursor blended with the thermoplastic polymer, and a plurality of nanoparticles disposed on the outer surface of each of the plurality of thermoplastic particles, wherein the metal precursor is capable of being activated to form a metal when exposed to laser irradiation, particularly using a pulsed laser. Optionally, at least some of the nanoparticles may be blended with the thermoplastic polymer so that a first portion of the nanoparticles is located within the thermoplastic particles and a second portion of the nanoparticles is disposed on the surface of the thermoplastic particles. The nanoparticles disposed on the outer surface of the thermoplastic particles may be at least partially embedded in and associated with the outer surface. When present, the nanoparticles disposed on the outer surface of the thermoplastic particles may facilitate easy distribution of the particulate composition during additive manufacturing.

[0032] When present, the plurality of nanoparticles may include a plurality of oxide nanoparticles. Suitable oxide nanoparticles for use in the present disclosure include, for example, silicon dioxide nanoparticles, titanium dioxide nanoparticles, zirconium oxide nanoparticles, aluminum oxide nanoparticles, iron oxide nanoparticles, copper oxide nanoparticles, tin oxide nanoparticles, boron oxide nanoparticles, cerium oxide nanoparticles, thallium oxide nanoparticles, tungsten oxide nanoparticles, or any combination thereof. The term "oxide" also encompasses mixed oxides such as aluminosilicates, borosilicates, and aluminoborosilicates. The nature of the oxide nanoparticles may be hydrophilic or hydrophobic, which may be natural for the nanoparticles or produced by surface treatment of the nanoparticles. For example, silicon dioxide nanoparticles with hydrophobic surface treatments (such as dimethylsilyl, trimethylsilyl, etc.) may be formed by reacting hydrophilic surface hydroxyls with suitable functionalizing agents. Hydrophobic functionalized oxide nanoparticles may be particularly desirable in the methods and particulate compositions of the present disclosure, but non-functionalized oxide nanoparticles or hydrophilically modified oxide nanoparticles may also be applicable.

[0033] Silica nanoparticles, particularly pyrogenic silica nanoparticles with hydrophobic functionalization thereon, may be particularly suitable for use in this disclosure, since a variety of functionalized silicas are available, wherein the type and particle size of the hydrophobic functionalization vary. Silazane and silane hydrophobic functionalizations are convenient hydrophobic functionalizations that may be used in this disclosure. Therefore, a plurality of oxide nanoparticles used in this disclosure may comprise silica nanoparticles, particularly hydrophobically functionalized silica nanoparticles, or may be substantially composed of silica nanoparticles. Silica nanoparticles may be used in conjunction with oxide nanoparticles or non-oxide nanoparticles of this other type, wherein the oxide or non-oxide nanoparticles of the other type may convey properties that are not obtainable when using separate silica nanoparticles to thermoplastic particles or objects formed by thermoplastic particles.

[0034] Carbon black is another type of nanoparticle that can be present on the thermoplastic particulate in this disclosure. Various grades of carbon black are familiar to those of ordinary skill in the art, and any of these grades of carbon black can be used in this disclosure. Other nanoparticles that can absorb infrared radiation can also be used similarly to facilitate the formation of thermoplastic particulates. In some cases, carbon black, silicon dioxide, and other types of oxide nanoparticles can be present in combination with each other.

[0035] Polymer nanoparticles are another type of nanoparticles that can be present on thermoplastic microparticles suitable for use in the present disclosure. Suitable polymer nanoparticles can include one or more polymers that are thermosetting and / or crosslinked so that they do not melt when processed by melt emulsification or similar microparticle formation techniques according to the present disclosure. Nanoparticles comprising high molecular weight thermoplastic polymers with high melting points or decomposition points can similarly represent suitable polymers for promoting thermoplastic microparticle formation in the present disclosure.

[0036] The loading capacity and granularity of silicon dioxide nanoparticles or similar oxide nanoparticles on thermoplastic particles can change in a wide range in the disclosure of this paper.The loading capacity of silicon dioxide nanoparticles or similar oxide nanoparticles can be determined by the nanoparticle concentration in the carrier fluid for promoting the formation of thermoplastic particles, as further described below.In non-limiting examples, the concentration of nanoparticles can be in the weight relative to thermoplastic polymer, about 0.01 % by weight to about 10 % by weight, or about 0.05 % by weight to about 10 % by weight, or about 0.05 % by weight to about 5 % by weight, or about 0.1 % by weight to about 2 % by weight, or about 0.25 % by weight to about 1.5 % by weight, or about 0.2 % by weight to about 1.0 % by weight, or about 0.25 % by weight to about 1 % by weight, or about 0.25 % by weight to about 0.5 % by weight.The granularity of nanoparticles can be in the range of about 1 nm to about 100 nm, but the granularity up to about 500 nm is also acceptable. In non-limiting examples, the particle size of the silica nanoparticles can be in the range of about 5 nm to about 75 nm, or about 5 nm to about 50 nm, or about 5 nm to about 10 nm, or about 10 nm to about 20 nm, or about 20 nm to about 30 nm, or about 30 nm to about 40 nm, or about 40 nm to about 50 nm, or about 50 nm to about 60 nm. Nanoparticles, particularly silica nanoparticles and similar oxide nanoparticles, can have a particle size of about 10 nm. 2 / g to about 500m 2 / g, or about 10m 2 / g to about 150m 2 / g, or about 25m 2 / g to about 100m 2 / g, or about 100m 2 / g to about 250m 2 / g, or about 250m 2 / g to about 500m 2 / g of BET surface area.

[0037] Specific silica nanoparticles suitable for the disclosure herein may be hydrophobically functionalized. Such hydrophobic functionalization may make the silica nanoparticles less compatible with water than non-functionalized silica nanoparticles. In addition, hydrophobic functionalization may improve the dispersibility of silica nanoparticles in a carrier fluid, which may be highly hydrophobic. Hydrophobic functionalization may be non-covalently or covalently attached to the surface of the silica nanoparticles. Covalent attachment may be performed, for example, by functionalization of surface hydroxyls on the surface of the silica nanoparticles. In a non-limiting example, hexamethyldisilazane may be used to treat the silica nanoparticles to provide hydrophobically modified covalent functionalization. Commercially available hydrophobically functionalized silica nanoparticles include, for example, Aerosil RX50 (Evonik, average particle size = 40nm) and Aerosil R812S (Evonik, average particle size = 7nm).

[0038] Oxide nanoparticles or non-oxide nanoparticles suitable for use in the present disclosure may also include those nanoparticles capable of absorbing infrared radiation. Exemplary materials capable of absorbing infrared radiation to promote the formation of a metal from a metal precursor are discussed further below.

[0039] The metal precursor may be incorporated into the thermoplastic particulate during melt emulsification or another suitable blending technique in which the thermoplastic polymer is softened or liquefied to form thermoplastic polymer droplets. Thus, suitable metal precursors may be thermally stable at a temperature greater than or equal to the melting point or softening temperature of the thermoplastic polymer. Other properties of suitable metal precursors may include, for example, non-conductivity (before conversion to metal), good weatherability, easy blending of the metal precursor particles with the thermoplastic polymer and / or solubility of the metal precursor in the thermoplastic polymer, and low toxicity. When incorporated as particles, the size of the metal precursor particles may be in the range of about 10 nm to about 1000 nm.

[0040] Particularly suitable metal precursors can be activated by lasers operating in the infrared region (including the near infrared region), the visible light region, or the ultraviolet region of the electromagnetic spectrum. Therefore, suitable laser irradiation wavelengths can be selected from those laser irradiation wavelengths residing in the range of about 200nm to about 14,000nm, especially irradiation wavelengths in the range of about 1020nm to about 1070nm. Suitable lasers, especially pulsed laser variants thereof, may include solid-state lasers, fiber lasers, semiconductor lasers (laser diodes), CO2 lasers (emitting wavelengths of 10,600nm) and excimer lasers operating in the ultraviolet region of the electromagnetic spectrum. When used to promote the activation of metal precursors, the CO2 laser may be operated under conditions different from those used to promote the consolidation of powder particles. Specifically, when promoting metal activation, the CO2 laser may be operated at a laser intensity higher than the laser intensity (laser power per unit area) used to promote the consolidation of powder particles. Due to the high laser intensity, the pulsed wave operation of the laser may be desirable when activating the metal precursor.

[0041] Frequency doubled or tripled Nd:YAG lasers or similar solid-state lasers can provide visible radiation (532 nm) or ultraviolet radiation (355 nm), while non-frequency doubled variants can provide near infrared radiation at 1064 nm. Other frequency doubled lasers can also be used in the disclosure herein.

[0042] The near-infrared region may be particularly suitable due to the availability of solid-state lasers or fiber lasers that provide electromagnetic radiation in this region of the electromagnetic spectrum. For example, suitable lasers operating in the near-infrared region of the electromagnetic spectrum include, for example, Nd (neodymium) doped solid-state lasers with an emission wavelength of about 1064 nm, such as Nd:YAG (yttrium aluminum garnet), Nd:YVO4 (yttrium orthovanadate), and Nd:YLF (yttrium lithium fluoride) lasers; solid-state lasers doped with other metals with an operating wavelength of about 1020 nm to about 1050 nm; and fiber lasers with an emission wavelength of about 1030 nm to about 1070 nm, such as Yb-doped fiber lasers. Lasers suitable for activating metal precursors for use in the present disclosure may be operated in a pulsed wave mode to provide high pulsed laser intensity to effectively convert metal precursors into metal islands, as well as to provide polymer surface ablation and roughening to promote strong metal adhesion. The specific example of suitable metal precursor can include those metal precursors that can be activated by pulsed laser beams with an emission wavelength in the range of about 1020nm to about 1070nm, and the emission wavelength is located in the near infrared region of the electromagnetic spectrum. Such lasers can operate at a power of about 1W to about 10W, a pulse frequency of about 10kHz to about 120kHz, and a scanning speed of about 0.1m / s to about 10m / s. The specific metal precursor used can determine the type of pulsed lasers used to form metal islands and their emission wavelengths, as described below for some specific examples.

[0043] Specific examples of suitable metal precursors may include one or more of the following materials:

[0044] - Copper oxide, or a mixed oxide of copper and a metal selected from the group consisting of antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium. Specific examples of mixed oxides of copper include, for example, copper oxide chromium spinel (copper chromite), copper aluminum oxide, copper iron oxide, etc. Copper chromite can be suitably activated, for example, at a pulsed laser emission wavelength of 1060 nm (such as using an Nd:YAG laser).

[0045] - Copper hydroxide, basic copper phosphate, copper phosphate, copper sulfate, copper thiocyanate, or any combination thereof. Unless otherwise specified, these copper salts contain copper in the +2 oxidation state (ortho-copper salts). Copper thiocyanate can exist in the +1 or +2 oxidation state.

[0046] -Metal organic complex (metal-ligand complex), the metal-organic complex comprising a metal selected from copper, silver, palladium or any combination thereof. Suitable metal-organic complexes may include, for example, metal monocarboxylate complexes, metal dicarboxylate complexes, metal acetylacetonate complexes, metal salicylaldimine complexes, and the like. Specific examples of suitable metal-organic complexes may include, but are not limited to, copper carboxylates and copper dicarboxylates, such as copper oxalate and copper oleate; copper acetylacetonate; salen copper (salen = N, N'-bis (salicylidene) ethylenediamine); silver carboxylates, such as silver neodecanoate; and palladium carboxylates, such as palladium acetate and palladium neodecanoate. Pulsed lasers emitting in the ultraviolet region of the electromagnetic spectrum (such as with an excimer laser) may be used to convert palladium-containing metal-organic complexes into metals. In contrast, some silver-containing metal-organic complexes may be suitably converted into metals using pulsed lasers emitting in the visible region of the electromagnetic spectrum.

[0047] Specific examples of metal precursors suitable for use in the present disclosure include, for example, PK3095 black pigment (Ferro Corporation) and Black 1G Pigment Black 28 (The Shepherd Color Company), both of which contain copper chromate spinel.

[0048] The intensity of absorption of infrared radiation (particularly infrared radiation in the near infrared region of the electromagnetic spectrum) by the metal precursor can determine whether irradiation with a pulsed laser results in sufficient conversion of the metal precursor to the corresponding metal. In the case where the absorption is sufficiently strong, the metal precursor may only be sufficient. If the infrared absorption intensity is weak, an infrared radiation absorber may also be blended with the thermoplastic polymer to promote a more efficient conversion of the metal precursor to a metal. Suitable infrared radiation absorbers may include, but are not limited to, non-stoichiometric metal oxides containing metals (e.g., antimony, bismuth, boron, copper, indium, titanium, tin, cesium, zirconium, molybdenum, vanadium, iron, or any combination thereof). Specific examples of suitable infrared radiation absorbers may include, for example, antimony-doped tin oxide, antimony-doped indium tin oxide; reduced indium tin oxide, oxygen-deficient bismuth oxide, and any combination thereof. When present, nanoparticles used to promote the formation of thermoplastic microparticles, especially oxide nanoparticles or carbon black, may constitute an infrared radiation absorber. That is, the infrared radiation absorber may be present in a plurality of nanoparticles used to promote the formation of thermoplastic microparticles, or may constitute a separate material. When present, the infrared radiation absorber may be included in the thermoplastic particulate in a loading of from about 0.01 wt % to about 10 wt % or from about 0.5 wt % to about 5 wt % relative to the thermoplastic polymer.

[0049] Depending on the intensity of infrared radiation absorption and the presence or absence of an infrared radiation absorber, the metal precursor may include from about 1 wt % to about 25 wt % of the plurality of thermoplastic particles as measured relative to the thermoplastic polymer; or from about 2 wt % to about 30 wt % of the plurality of thermoplastic particles as measured relative to the thermoplastic polymer, or from about 5 wt % to about 15 wt % of the plurality of thermoplastic particles.

[0050] Examples of thermoplastic polymers suitable for use in the present disclosure include, but are not limited to, polyamides (e.g., nylon-6, nylon-12, etc.), polyurethanes, polyethylenes, polypropylenes, polyacetals, polycarbonates, polyethylene terephthalates, polybutylene terephthalates, polystyrenes, polyvinyl chlorides, polytetrafluoroethylenes, polyesters (e.g., polylactic acid), polyethers, polyethersulfones, polyetheretherketones, polyacrylates, polymethacrylates, polyimides, acrylonitrile butadiene styrene (ABS), polyphenylene sulfide, vinyl polymers, polyarylethers, polyarylene sulfides, polysulfones, polyetherketones, polyaryletherketones (PAEK), polyamide-imides, polyetherimides, polyetheresters, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amides), grafted or non-grafted thermoplastic polyolefins, functionalized or non-functionalized Functionalized ethylene / vinyl monomer polymers, functionalized or non-functionalized ethylene / (meth) acrylate alkyl esters, functionalized or non-functionalized (meth) acrylic polymers, functionalized or non-functionalized ethylene / vinyl monomer / (meth) acrylate alkyl ester terpolymers, ethylene / vinyl monomer / carbonyl terpolymers, ethylene / (meth) acrylate alkyl ester / carbonyl terpolymers, methyl methacrylate-butadiene-styrene (MBS) core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, chlorinated or chlorosulfonated polyethylene, polyvinylidene fluoride (PVDF), phenolic resins, poly(ethylene / vinyl acetate), polybutadiene, polyisoprene, styrenic block copolymers, polyacrylonitrile, silicones, and the like, and any combination thereof. Copolymers comprising one or more of the foregoing substances may also be used in the present disclosure.

[0051] Particularly suitable examples of thermoplastic polymers for use in the present disclosure may include polyamides, such as nylon 6 or nylon 12; acrylonitrile butadiene styrene; polylactic acid; polyurethane; poly(arylene ether); polyaryletherketone; polycarbonate; polyimide; polyphenylene sulfide; poly(arylene sulfone); polyesters, such as polyethylene terephthalate or polybutylene terephthalate; and any combination thereof.

[0052] More specific examples of suitable polyamides include, but are not limited to, polycaprolactam (nylon 6, polyamide 6, or PA6), poly(hexamethylene succinamide) (nylon 46, polyamide 46, or PA46), polyhexamethylene adipamide (nylon 66, polyamide 66, or PA66), polypentamethylene adipamide (nylon 56, polyamide 56, or PA56), polyhexamethylene sebacamide (nylon 610, polyamide 610, or PA610), polyundecanamide (nylon 11, polyamide 11, or PA11), polydodecaneamide (nylon 12, polyamide 12, or PA12), and polyhexamethylene terephthalamide (nylon 6T, polyamide 6T, or PA6 T), nylon 10.10 (polyamide 10.10 or PA10.10), nylon 10.12 (polyamide 10.12 or PA10.12), nylon 10.14 (polyamide 10.14 or PA10.14), nylon 10.18 (polyamide 10.18 or PA10.18), nylon 6.10 (polyamide 6.10 or PA6.10), nylon 6.18 (polyamide 6.18 or PA6.18), nylon 6.12 (polyamide 6.12 or PA6.12), nylon 6.14 (polyamide 6.14 or PA6.14), semi-aromatic polyamides, and the like, and any combination thereof. Copolyamides may also be used. Examples of suitable copolyamides include, but are not limited to, PA11 / 10.10, PA 6 / 11, PA 6.6 / 6, PA 11 / 12, PA 10.10 / 10.12, PA 10.10 / 10.14, PA 11 / 10.36, PA 11 / 6.36, PA 10.10 / 10.36, etc. and any combination thereof. Polyesteramides, polyetheresteramides, polycarbonate-esteramides and polyether-block-amides may also be used, which may be elastomeric.

[0053] Examples of suitable polyurethanes include, but are not limited to, polyether polyurethanes, polyester polyurethanes, mixed polyether and polyester polyurethanes, and the like, and any combination thereof. Examples of suitable polyurethanes include, but are not limited to, poly[4,4'-methylenebis(phenyl isocyanate)-alternative-1,4-butanediol / di(propylene glycol) / polycaprolactone], 1190A (a polyether polyurethane elastomer available from BASF), 1190A10 (a polyether polyurethane elastomer available from BASF), etc. and any combination thereof.

[0054] Suitable thermoplastic polymers may be elastomeric or non-elastomeric. Some of the foregoing examples of thermoplastic polymers may be elastomeric or non-elastomeric, depending on the specific composition of the polymer. For example, polyethylene, which is a copolymer of ethylene and propylene, may be elastomeric and independent of the amount of propylene present in the polymer.

[0055] Elastomeric thermoplastic polymers generally belong to one of six categories: styrenic block copolymers, thermoplastic polyolefin elastomers, thermoplastic vulcanizates (also known as elastomeric alloys), thermoplastic polyurethanes, thermoplastic copolyesters, and thermoplastic polyamides (generally block copolymers containing polyamides), any of which may be used in the disclosure herein. Examples of elastomeric thermoplastic polymers may be found in the following document: Handbook of Thermoplastic Elastomers, 2nd edition, edited by BMW Walker and CP Rader, Van Nostrand Reinhold, New York, 1988. Examples of elastomeric thermoplastic polymers include, but are not limited to, elastic polyamides, polyurethanes, copolymers comprising polyether blocks and polyamide blocks (PEBA or polyether block amides), methyl methacrylate-butadiene-styrene (MBS) core-shell polymers, polystyrene-block-polybutadiene-block-poly(methyl methacrylate) (SBM) block terpolymers, polybutadiene, polyisoprene, styrenic block copolymers and polyacrylonitrile, silicones, and the like. Elastic styrenic block copolymers may include at least one block selected from the following: isoprene, isobutylene, butene, ethylene / butene, ethylene-propylene, and ethylene-ethylene / propylene. More specific examples of elastic styrenic block copolymers include, but are not limited to, poly(styrene-ethylene / butylene), poly(styrene-ethylene / butylene-styrene), poly(styrene-ethylene / propylene), poly(styrene-ethylene / propylene-styrene), poly(styrene-ethylene / propylene-styrene), poly(styrene-ethylene / propylene-styrene-ethylene-propylene), poly(styrene-butadiene-styrene), poly(styrene-butylene-butadiene-styrene), and the like, and any combination thereof.

[0056] In a non-limiting example, the thermoplastic microparticles disclosed herein can be formed by melt emulsification. Such methods for producing thermoplastic microparticles may include mixing a thermoplastic polymer and a metal precursor in a carrier fluid at a heated temperature at or above the melting point or softening temperature of the thermoplastic polymer; wherein the thermoplastic polymer and the carrier fluid are substantially immiscible at the heated temperature, and the metal precursor is capable of being activated to form metal islands when exposed to laser irradiation (such as a pulsed laser); applying sufficient shear at the heated temperature in the presence of the metal precursor to disperse the thermoplastic polymer as liquefied droplets; after forming the liquefied droplets, cooling the carrier fluid to at least a temperature to form thermoplastic microparticles in a solidified state, the thermoplastic microparticles comprising the thermoplastic polymer and at least a portion of the metal precursor blended with the thermoplastic polymer; and separating the thermoplastic microparticles from the carrier fluid. More specific examples of such methods may include mixing a thermoplastic polymer, nanoparticles, and a metal precursor in a carrier fluid at a heated temperature at or above the melting point or softening temperature of the thermoplastic polymer; wherein the thermoplastic polymer and the carrier fluid are substantially immiscible at the heated temperature, and the metal precursor is capable of being activated to form metal islands upon exposure to laser irradiation (such as a pulsed laser); applying sufficient shear at the heated temperature to disperse the thermoplastic polymer as liquefied droplets in the presence of the nanoparticles and the metal precursor; after the liquefied droplets are formed, cooling the carrier fluid to at least a temperature to form solidified thermoplastic particles comprising the thermoplastic polymer, at least a portion of the metal precursor blended with the thermoplastic polymer, and at least a portion of the nanoparticles associated with the outer surface of each of the thermoplastic particles; and separating the thermoplastic particles from the carrier fluid. Optionally, the infrared radiation absorber can be combined with the thermoplastic polymer, nanoparticles and metal precursors in the carrier fluid so that the infrared radiation absorber is blended with the thermoplastic microparticles after the thermoplastic microparticles are formed. Suitable examples of thermoplastic polymers, nanoparticles, metal precursors and infrared radiation absorbers are provided above, any of which can be used to form thermoplastic microparticles according to the disclosure herein.

[0057] Figure 11 is a flow chart of a non-limiting example method 100 for producing thermoplastic microparticles according to the present disclosure, wherein microparticle formation occurs in the presence of nanoparticles. As shown, a thermoplastic polymer 102, a carrier fluid 104, nanoparticles 106, and a metal precursor 107 are combined at 108 to produce a mixture 110. One or more surfactants, such as one or more sulfonate surfactants, may also be present in the mixture 110. The thermoplastic polymer 102, the carrier fluid 104, the nanoparticles 106, and the metal precursor 107 may be combined in any order at 108 and mixed and / or heated. In a particular example, the carrier fluid 104 may be heated to a temperature above the melting point or softening temperature of the thermoplastic polymer before the other components are combined with the thermoplastic polymer 102.

[0058] Heating to a melting point or softening temperature higher than the thermoplastic polymer 102 can be performed at any temperature lower than the decomposition temperature or boiling point of any component in the molten emulsion. In a non-limiting example, heating can be performed at a temperature of about 1°C to about 50°C, or about 1°C to about 25°C, or about 5°C to about 30°C, or about 20°C to about 50°C higher than the melting point or softening temperature of the thermoplastic polymer 102. In the disclosure herein, a 10°C / min ramp rate and a cooling rate can be used to determine the melting point by ASTME794-06 (2018). Unless otherwise specified, the softening temperature or softening point of the polymer is determined by ASTM D6090-17. The softening temperature can be measured using a cup-ball apparatus available from Mettler-Toledo, using a 0.50 gram sample at a heating rate of 1°C / min. The melting point or softening temperature in the present disclosure can be in the range of about 50°C to about 400°C.

[0059] The mixture 110 is then processed at 112 by applying sufficient shear at a temperature greater than the melting point or softening temperature of the thermoplastic polymer 102 to produce liquefied droplets of the thermoplastic polymer 102, thereby forming a molten emulsion 114. Without being limited by theory, it is believed that increasing shear can reduce the size of the liquefied droplets in the carrier fluid 104, all other factors being equal. It should be understood that there may be diminishing returns to increasing shear and subsequently reducing droplet size at a certain point, and / or damage to the droplet contents may occur at higher shear rates. Examples of mixing devices suitable for producing the molten emulsion 114 include, but are not limited to, extruders (e.g., continuous extruders, batch extruders, etc.), stirred reactors, mixers, reactors with in-line homogenizer systems, and the like, and devices derived therefrom.

[0060] In non-limiting examples, the size of the liquefied droplets may be from about 1 μm to about 1,000 μm, or from about 1 μm to about 500 μm, or from about 1 μm to about 200 μm, or from about 1 μm to about 150 μm, or from about 1 μm to about 130 μm, or from about 1 μm to about 100 μm, or from about 10 μm to about 150 μm, or from about 10 μm to about 100 μm, or from about 20 μm to about 80 μm, or from about 20 μm to about 50 μm, or from about 50 μm to about 90 μm. The resulting thermoplastic microparticles formed after solidification may reside in a similar size range. That is, the size of the thermoplastic microparticles in the microparticle compositions and methods of the present disclosure can be from about 1 μm to about 1,000 μm, or from about 1 μm to about 500 μm, or from about 1 μm to about 200 μm, or from about 1 μm to about 150 μm, or from about 1 μm to about 130 μm, or from about 1 μm to about 100 μm, or from about 1 μm to about 200 μm, or from about 10 μm to about 100 μm, or from about 20 μm to about 80 μm, or from about 20 μm to about 50 μm, or from about 50 μm to about 90 μm. Particle size measurements can be made by analyzing optical images or using the onboard software of a Malvern Mastersizer 3000 Aero S instrument, which uses a light scattering technique for particle size measurements.

[0061] For light scattering techniques, the Quality Audit Standards (QAS4002) can be used. TM Glass bead control samples with diameters ranging from 15 μm to 150 μm were purchased from Malvern Analytical Ltd. Samples can be analyzed as dry powders dispersed in air using the dry powder dispersion module of a Mastersizer 3000 Aero S. Particle size can be derived from a plot of bulk density versus size using the instrument software.

[0062] The molten emulsion 114 is then cooled 116 to solidify the liquefied droplets into thermoplastic particles in a solidified state. The cooling rate may be in the range of about 100°C / second to about 10°C / hour or about 10°C / second to about 10°C / hour, including any cooling rate therebetween. Shearing may be interrupted during cooling, or may be maintained at the same rate or at different rates during cooling. The cooled mixture 118 may then be processed at 120 to separate the thermoplastic particles 122 from other components 124 (e.g., carrier fluid 104, excess nanoparticles 106, excess metal precursors 107, etc.). Washing, filtering, and / or similar operations may be performed at this stage to further purify the thermoplastic particles 122, wherein the thermoplastic particles 122 include the thermoplastic polymer 102, at least a portion of the nanoparticles 106 coating the outer surface of the thermoplastic particles 122, and at least a portion of the metal precursors 107 mixed or associated within the thermoplastic particles 122. Depending on non-limiting factors such as temperature (including cooling rate), type of thermoplastic polymer 102, and type and size of nanoparticles 106, nanoparticles 106 may become at least partially embedded within the outer surface of thermoplastic particles 122 during the process of becoming disposed on the outer surface of the thermoplastic particles 122. Even if embedding does not occur, nanoparticles 106 may remain robustly associated with thermoplastic particles 122 to facilitate their further use. Metal precursors 107 may be disposed on the surface of thermoplastic particles 122, blended as a solid with the thermoplastic particles in a polymer matrix, or dissolved within a polymer matrix.

[0063] In the foregoing, the thermoplastic polymer 102 and the carrier fluid 104 are selected such that the components are immiscible or substantially immiscible (<5 wt % solubility), particularly <1 wt % solubility, at various processing temperatures (e.g., from room temperature to temperatures at which liquefied droplets form and remain as two or more phases).

[0064] After the thermoplastic particles 122 are separated from the other components 124, further processing 126 of the thermoplastic particles 122 may be performed. In a non-limiting example, the further processing 126 may include, for example, screening the thermoplastic particles 122 and / or blending the thermoplastic particles 122 with other substances to form processed thermoplastic particles 128. The processed thermoplastic particles 128 may be formulated for a desired application, such as additive manufacturing in a non-limiting example.

[0065] Thermoplastic particles may have a particle size of about 0.3 g / cm 3 To about 0.8g / cm 3 , or about 0.3g / cm 3 To about 0.6g / cm 3 , or about 0.4g / cm 3 To about 0.7g / cm 3 , or about 0.5g / cm 3To about 0.6g / cm 3 , or about 0.5g / cm 3 To about 0.8g / cm 3 The bulk density.

[0066] In a specific example of the present disclosure, a shear sufficient to form liquefied droplets can be applied by stirring the carrier fluid. In a non-limiting example, the stirring rate can be in the range of about 50 revolutions per minute (RPM) to about 1500RPM, or about 250RPM to about 1000RPM, or about 225RPM to about 500RPM. The stirring rate when melting the thermoplastic polymer can be the same or different from the stirring rate used after the liquefied droplets have been formed. The liquefied droplets can be stirred in a stirring time of about 30 seconds to about 18 hours or longer, or about 1 minute to about 180 minutes, or about 1 minute to about 60 minutes, or about 5 minutes to about 6 minutes, or about 5 minutes to about 30 minutes, or about 10 minutes to about 30 minutes, or about 30 minutes to about 60 minutes.

[0067] The load (concentration) of the thermoplastic polymer in the carrier fluid can vary in a wide range. In a non-limiting example, the load of the thermoplastic polymer in the carrier fluid can be in the range of about 1 wt % to about 99 wt % relative to the weight of the carrier fluid. In a more specific example, the load of the thermoplastic polymer can be in the range of about 5 wt % to about 75 wt %, or about 10 wt % to about 60 wt %, or about 20 wt % to about 50 wt %, or about 20 wt % to about 30 wt %, or about 30 wt % to about 40 wt %, or about 40 wt % to about 50 wt %, or about 50 wt % to about 60 wt %. Thermoplastic polymer can be present in the range of about 5 wt % to about 60 wt %, or about 5 wt % to about 25 wt %, or about 10 wt % to about 30 wt %, or about 20 wt % to about 45 wt %, or about 25 wt % to about 50 wt %, or about 40 wt % to about 60 wt %.

[0068] After forming thermoplastic microparticles in the presence of nanoparticles according to the disclosure herein, at least a portion of the nanoparticles (such as silica nanoparticles or other oxide nanoparticles) can be disposed on the outer surface of the thermoplastic microparticles as a coating or partial coating. The coating can be substantially uniformly disposed on the outer surface. As used herein with respect to the coating, the term "substantially uniform" refers to a uniform coating thickness in the surface position (particularly the entire outer surface) covered by the nanoparticles. The coating coverage on the thermoplastic microparticles can be in the range of about 5% to about 100% of the microparticle surface area, or about 5% to about 25%, or about 20% to about 50%, or about 40% to about 70%, or about 50% to about 80%, or about 60% to about 90%, or about 70% to about 100%. Coverage can be determined by image analysis of SEM micrographs.

[0069] Carrier fluids suitable for use in the present disclosure include those in which the thermoplastic polymer is substantially immiscible with the carrier fluid, the carrier fluid having a boiling point above the melting point or softening temperature of the thermoplastic polymer, and the carrier fluid having sufficient viscosity to form liquefied droplets of substantially spherical shape after the thermoplastic polymer has melted therein. Suitable carrier fluids may include, for example, silicone oil, fluorinated silicone oil, perfluorinated silicone oil, polyethylene glycol, polyethylene glycol with an alkyl terminal (e.g., a C1-C4 terminal alkyl group such as tetraethylene glycol dimethyl ether (TDG)), paraffin, liquid petrolatum, vison oil, turtle oil, soybean oil, perhydrosqualene, sweet almond oil, calophyllum oil, palm oil, parleam oil, grape seed oil, sesame oil, corn oil, rapeseed oil, sunflower oil, cottonseed oil, almond oil, castor oil, avocado oil, jojoba oil, olive oil, corn germ oil, esters of lanolic acid, esters of oleic acid, esters of lauric acid, esters of stearic acid, fatty acid esters, higher fatty acids, fatty alcohols, polysiloxanes modified with fatty acids, polysiloxanes modified with fatty alcohols, polysiloxanes modified with polyoxyalkylenes, and the like, and any combination thereof.

[0070] Suitable carrier fluids may have a viscosity of about 0.6 g / cm 3 To about 1.5g / cm 3 Thermoplastic polymers may have a density of about 0.7 g / cm 3 To about 1.7g / cm 3 wherein the thermoplastic polymer has a similar, lower or higher density than the density of the carrier fluid.

[0071] Particularly suitable silicone oils are polysiloxanes. Exemplary silicone oils suitable for use in the present disclosure include, for example, polydimethylsiloxane (PDMS), methylphenyl polysiloxane, alkyl-modified polydimethylsiloxane, alkyl-modified methylphenyl polysiloxane, amino-modified polydimethylsiloxane, amino-modified methylphenyl polysiloxane, fluorine-modified polydimethylsiloxane, fluorine-modified methylphenyl polysiloxane, polyether-modified polydimethylsiloxane, polyether-modified methylphenyl polysiloxane, and the like, and any combination thereof.

[0072] In a non-limiting example, the carrier fluid and the thermoplastic polymer may be heated at a temperature of about 200° C. or higher. A suitable heating temperature may be selected based on the melting point or softening temperature of the thermoplastic polymer and the boiling point of the carrier fluid. The cooling rate after the formation of the liquefied polymer droplets may be varied as desired. In some cases, cooling may be performed by dissipating heat to the surrounding environment at an inherent (uncontrolled) rate after the heating is interrupted. In other cases, cooling at a controlled rate may be employed (e.g., by gradually reducing the heating temperature and / or using jacket temperature control to increase or decrease the cooling rate).

[0073] Suitable carrier fluids, such as polysiloxanes, including PDMS, may have a viscosity of about 1,000 cSt to about 150,000 cSt, or about 1,000 cSt to about 60,000 cSt, or about 40,000 cSt to about 100,000 cSt, or about 75,000 cSt to about 150,000 cSt at 25° C. The viscosity of the carrier fluid may be obtained from commercial suppliers or, if desired, may be measured by techniques known to those of ordinary skill in the art.

[0074] The thermoplastic particles may be separated from the carrier fluid by any of a variety of known separation techniques. Any of gravity settling and filtration, decanting, centrifugation, and the like may be used to separate the thermoplastic particles from the carrier fluid. The thermoplastic particles may be washed with a solvent in which the carrier fluid is soluble and the thermoplastic particles are not soluble during the separation process. Additionally, a solvent in which the carrier fluid is soluble and the thermoplastic particles are not soluble may be mixed with the carrier fluid and the thermoplastic particles prior to the initial separation of the thermoplastic particles from the carrier fluid.

[0075] Suitable solvents for washing the thermoplastic particulates or mixing with the carrier fluid may include, but are not limited to, aromatic hydrocarbons (e.g., toluene and / or xylene), aliphatic hydrocarbons (e.g., heptane, n-hexane and / or n-octane), cyclic hydrocarbons (e.g., cyclopentane, cyclohexane and / or cyclooctane), ethers (e.g., diethyl ether, tetrahydrofuran, diisopropyl ether and / or dioxane), halogenated hydrocarbons (e.g., dichloroethane, trichloroethane, dichloromethane, chloroform and / or carbon tetrachloride), alcohols (e.g., methanol, ethanol, isopropanol and / or n-propanol), ketones (e.g., methyl ethyl ketone and / or acetone); esters (e.g., ethyl acetate, etc.), water, etc., and any combination thereof. After washing the thermoplastic particulates, any one of heating, vacuum drying, air drying, or any combination thereof may be performed.

[0076] At least most of the thermoplastic microparticles obtained according to the disclosure herein may be substantially spherical in shape. More typically, about 90% or more, or about 95% or more, or about 99% or more of the thermoplastic microparticles prepared by melt emulsification according to the present disclosure may be substantially spherical in shape. In other non-limiting examples, the thermoplastic microparticles of the present disclosure may have a sphericity (roundness) of about 0.9 or more, including about 0.90 to about 1.0, or about 0.93 to about 0.99, or about 0.95 to about 0.99, or about 0.97 to about 0.99, or about 0.98 to 1.0. The sphericity (roundness) can be measured using a Sysmex FPIA-2100 flow particle image analyzer. In order to determine the roundness, an optical microscopic image is taken of the microparticles. The circumference (P) and area (A) of the microparticles in the plane of the microscopic image are calculated (for example, using a SYSMEX FPIA 3000 particle shape and size analyzer, available from Malvern Instruments). The circularity of the microparticles is C EA / P, where C EA It is the circumference of a circle whose area is equal to the area (A) of the actual particle.

[0077] The thermoplastic microparticles of the present disclosure may have an angle of repose of about 25° to about 45°, or about 25° to about 35°, or about 30° to about 40°, or about 35° to about 45°. The angle of repose may be determined using ASTM D6393-14 "Standard Test Method for Bulk Solids Characterized by Carr Indices" using a Hosokawa Micron Powder Characterization Tester PT-R.

[0078] Thermoplastic particles separated from the carrier fluid according to the above disclosure can be further processed to make the thermoplastic particles suitable for the intended application. In one example, the thermoplastic particles can pass through a sieve or similar structure having an effective screening size greater than the average particle size of the thermoplastic particles. For example, an exemplary screening size for processing thermoplastic particles suitable for three-dimensional printing can have an effective screening size of about 150 μm. When referring to screening, the hole / sieve size is described in accordance with the American Standard Sieve (ASTME11-17). Other screening sizes (larger or smaller) may be more suitable for thermoplastic particles designated for other applications. Screening can remove larger particles that may have been formed during the melt emulsification process, and / or remove agglomerated particles that may have poor flow characteristics. Generally speaking, a sieve with an effective screening size in the range of about 10 μm to about 250 μm can be used.

[0079] In addition, the thermoplastic particles, including the sieved thermoplastic particles, can be mixed with one or more additional components, such as flow aids, fillers or other substances intended to tailor the properties of the thermoplastic particles for the intended application. The mixing of the additional components with the thermoplastic particles can be carried out by dry blending techniques. Suitable examples of flow aids (e.g., carbon black, graphite, silica, etc.) and similar substances are familiar to those of ordinary skill in the art.

[0080] In certain applications, the particulate compositions disclosed herein can be used in additive manufacturing processes, particularly those that employ selective laser sintering or other powder bed fusion processes to promote particulate consolidation. Such printed objects initially obtained from selective laser sintering may be characterized in that the metal precursor remains substantially unconverted to metal. Any metal precursor that is indeed activated during selective laser sintering is not believed to result in the production of coherent metal islands for forming one or more conductive traces. Subsequently, laser irradiation (such as that provided by a pulsed laser and described in more detail above) can be used to convert the metal precursor in the printed object into metal (e.g., a plurality of discontinuous metal islands) in a desired pattern. The metal islands can then be interconnected by chemical plating to form one or more conductive traces on the surface of the printed object.

[0081] Thus, the additive manufacturing process of the present disclosure may include: depositing a particulate composition in a powder bed, the particulate composition comprising a plurality of thermoplastic particles, the plurality of thermoplastic particles comprising a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, wherein the metal precursor is capable of being activated to form metal islands when exposed to laser irradiation (such as using a pulsed laser); and consolidating a portion of the plurality of thermoplastic particles in the powder bed, such as by performing selective laser sintering, to form a printed object, in which the metal precursor remains substantially unconverted to metal. In a more specific example, the nanoparticles may be present on the thermoplastic particles, such that the additive manufacturing process includes depositing a particulate composition in a powder bed, the particulate composition comprising a plurality of thermoplastic particles, the plurality of thermoplastic particles comprising a thermoplastic polymer, a metal precursor blended with the thermoplastic polymer, and a plurality of nanoparticles disposed on an outer surface of each of the plurality of thermoplastic particles, wherein the metal precursor is capable of being activated to form a metal when exposed to laser irradiation (such as with a pulsed laser); and consolidating a portion of the plurality of thermoplastic particles in the powder bed, such as by performing selective laser sintering, to form a printed object in which the metal precursor remains substantially unconverted to metal. More specifically, the printed object produced in the foregoing manner may be formed by consolidating the thermoplastic particles in the powder bed by exposure to a laser that substantially does not convert the metal precursor to metal or converts it very limitedly. Such printed objects may comprise: a polymer matrix formed by consolidation of microparticles and comprising a thermoplastic polymer; and a metal precursor and optional nanoparticles blended with the polymer matrix, wherein the metal precursor is capable of being activated to form a metal when exposed to laser irradiation (such as using a pulsed laser).

[0082] It is believed that suitable conditions for performing selective laser sintering or other powder bed particle consolidation processes to form printed objects are not particularly limited, provided that particle consolidation also does not promote the conversion of metal precursors to metals. Lasers suitable for performing selective laser sintering in this manner may include both continuous wave lasers and pulsed wave lasers, either of which can provide the energy required to promote the consolidation of powder particles. Due to the high absorptivity of polymers to the wavelength of CO2 laser emission, CO2 lasers are often used to promote the consolidation of polymer powder particles. The operating conditions of the CO2 laser can be selected so that particle consolidation occurs in priority to the activation of the metal precursor. Standard laser settings (e.g., power, scan rate, bed temperature, etc.) for promoting the consolidation of polymer particles can be selected based on the specific thermoplastic polymer present, and suitable laser settings can be selected by a person of ordinary skill in the art. The selection of specific conditions for performing selective laser sintering or similar powder consolidation techniques can be affected by non-limiting factors such as the type of thermoplastic polymer used, the size and composition of the thermoplastic particles, the type of printed object produced, and the expected use conditions of the printed object.

[0083] Examples of printed objects that may be formed using the particulate compositions disclosed herein are considered to be not particularly limited, and may include, for example, containers (e.g., for food, beverages, cosmetics, personal care compositions, pharmaceuticals, etc.), shoe soles, toys, furniture components, decorative household items, plastic gears, screws, nuts, bolts, cable ties, medical supplies, prostheses, orthopedic implants, preparation of artifacts to aid learning in education, 3D anatomical models to aid surgery, robotics, biomedical devices (orthotics), household appliances, dentistry, automotive and aircraft / aerospace components, electronic devices, sporting goods, etc. Many of these printed objects may benefit from the introduction of one or more conductive traces thereon, as described below.

[0084] According to the disclosure herein, after forming a printed object comprising a metal precursor, a portion of the metal precursor may be converted into metal islands, which may subsequently be converted into one or more metal traces. More specifically, the method of the present disclosure may include activating a portion of the metal precursor within the printed object using laser irradiation (particularly a pulsed laser) to form a plurality of discontinuous metal islands in a predetermined pattern on the surface of the printed object. Suitable pulsed lasers may include, but are not limited to, Nd:YAG lasers, vanadate lasers, and fiber lasers. Other suitable lasers and conditions for promoting metal formation are specified above.

[0085] After forming the discontinuous metal islands, the metal islands can be interconnected to form one or more conductive traces by performing chemical plating. The one or more conductive traces are conductive and can be formed by a variety of suitable metals (such as copper, silver, gold or nickel). In a non-limiting example, the multiple conductive traces can be separated by about 150 μm or less from each other. Suitable chemical plating conditions will be familiar to those of ordinary skill in the art and can be used in the disclosure of this article. For example, copper ethylenediaminetetraacetic acid copper complex (Cu-EDTA) / formaldehyde can be used to plate copper under electroless conditions. In another specific example, copper-nickel alloys can be plated under electroless conditions using copper hypophosphite in the presence of nickel ions as a mediator. Nickel can be plated under electroless conditions using nickel salts (e.g., nickel sulfate) and reducing agents (such as hypophosphites or borohydrides).

[0086] Figure 2 An illustrative process schematic diagram showing the formation of a printed object by performing selective laser sintering and then activating a metal precursor, as viewed from the top of the printed object, is shown. As shown, method 200 includes forming a powder bed 202, which includes unconsolidated thermoplastic particles 204 and a consolidated thermoplastic matrix 206, the latter of which is formed by laser irradiation 212 from a laser 210 (such as a CO2 continuous laser). Laser 214 is a pulsed laser and is different from laser 210, so that laser 214 does not play a role in the consolidation of the particles to form the consolidated thermoplastic matrix 206. Generally speaking, laser 214 is not activated during the consolidation of the particles. Although Figure 2 Lasers 210 and 214 have been depicted as being operated separately to facilitate particle consolidation and metal island formation, but it should also be understood from the above description that a single laser may be utilized under different operating conditions to separately consolidate powder particles and facilitate metal island formation.

[0087] In metal conversion 220, the consolidated thermoplastic matrix 206 is selectively irradiated with a pulsed laser beam 216 from a laser 214 to define metal islands 222 in a desired pattern on the surface of the consolidated thermoplastic matrix 206. Thereafter, the consolidated thermoplastic matrix 206 can be separated from the unconsolidated thermoplastic particles 204 to provide a printed object 230 having metal islands 222 defined thereon. Alternatively, the printed object 230 can be released from the powder bed 202 before the metal islands 222 are defined thereon, in which case the laser 214 can be located in a separate production line. In a particular process configuration, the laser 214 can be a near-infrared pulsed laser. Electroless plating 240 can then be performed to define conductive traces 242 in a desired pattern on the surface of the printed object 230.

[0088] Embodiments disclosed herein include:

[0089] A. Microparticle compositions comprising powder particles. The microparticle compositions comprise: a plurality of thermoplastic microparticles comprising a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation.

[0090] B. Printed object. The printed object comprises: a polymer matrix formed by consolidation of microparticles and comprising a thermoplastic polymer; and a metal precursor admixed with the polymer matrix, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation.

[0091] C. A method for forming a printed object by particle consolidation. The method comprises: depositing a particle composition in a powder bed, the particle composition comprising a plurality of thermoplastic particles, the plurality of thermoplastic particles comprising a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation; and consolidating a portion of the plurality of thermoplastic particles in the powder bed to form a printed object, in which the metal precursor remains substantially unconverted to metal.

[0092] D. A method for forming powder particles. The method comprises: mixing a thermoplastic polymer with a metal precursor in a carrier fluid at a heated temperature at or above the melting point or softening temperature of the thermoplastic polymer; wherein the thermoplastic polymer and the carrier fluid are substantially immiscible at the heated temperature, and the metal precursor is capable of being activated to form metal islands when exposed to laser irradiation; applying sufficient shear at the heated temperature in the presence of the metal precursor to disperse the thermoplastic polymer as liquefied droplets; after the liquefied droplets are formed, cooling the carrier fluid to at least a temperature to form thermoplastic particles in a solidified state, the thermoplastic particles comprising the thermoplastic polymer and at least a portion of the metal precursor admixed with the thermoplastic polymer; and separating the thermoplastic particles from the carrier fluid.

[0093] Each of embodiments A, B, C, and D may have one or more of the following additional elements in any combination:

[0094] Element 1: wherein the particulate composition further comprises a plurality of nanoparticles, the plurality of nanoparticles being disposed on an outer surface of each of the plurality of thermoplastic particles, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof.

[0095] Element 1A: wherein the printed object further comprises a plurality of nanoparticles, the plurality of nanoparticles being blended with the polymer matrix, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof.

[0096] Element 1B: wherein the plurality of thermoplastic particles further comprises a plurality of nanoparticles disposed on an outer surface of each of the plurality of thermoplastic particles, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof.

[0097] Element 1C: wherein the method further comprises combining nanoparticles with the thermoplastic polymer and the metal precursor in the carrier fluid, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof; wherein at least a portion of the nanoparticles are disposed on an outer surface of each of the thermoplastic particles.

[0098] Element 2: wherein the plurality of oxide nanoparticles include a plurality of silicon dioxide nanoparticles.

[0099] Element 3: wherein the metal precursor is thermally stable at a temperature greater than or equal to the melting point or softening temperature of the thermoplastic polymer.

[0100] Element 4: wherein the metal precursor can be activated by an infrared or near-infrared pulsed laser.

[0101] Element 5: wherein the metal precursor is capable of being activated at a wavelength ranging from about 1020 nm to about 1070 nm.

[0102] Element 6: wherein the metal precursor comprises at least one material selected from the group consisting of: copper oxide; mixed oxides of copper and a metal, the metal being selected from the group consisting of: antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium; copper chromium oxide spinel; copper aluminum oxide; copper hydroxide; basic copper phosphate; copper phosphate; copper sulfate; copper thiocyanate; a metal-organic complex, the metal-organic complex comprising a metal selected from the group consisting of: copper, silver, palladium and any combination thereof; and any combination thereof.

[0103] Element 7: wherein the microparticle composition further comprises an infrared radiation absorber blended with the thermoplastic polymer.

[0104] Element 7A: wherein the printed object further comprises an infrared radiation absorber blended with the polymer matrix.

[0105] Element 7B: wherein the plurality of thermoplastic particles further comprises an infrared radiation absorber blended with the thermoplastic polymer.

[0106] Element 7C: wherein the method further comprises combining an infrared radiation absorber in the carrier fluid, the infrared radiation absorber being blended with the thermoplastic polymer in the thermoplastic microparticles.

[0107] Element 8: wherein the infrared radiation absorber comprises a non-stoichiometric metal oxide.

[0108] Element 9: wherein the metal precursor is soluble in the thermoplastic polymer or dispersed in the thermoplastic polymer as microparticles, the microparticles having a particle size ranging from about 10 nm to about 1000 nm.

[0109] Element 10: wherein the plurality of thermoplastic particles comprises about 1 wt % to about 25 wt % of the metal precursor.

[0110] Element 10A: wherein the polymer matrix comprises from about 1 wt % to about 25 wt % of the metal precursor.

[0111] Element 10B: wherein the plurality of thermoplastic particles comprises from about 1 wt % to about 25 wt % of the metal precursor.

[0112] Element 11: wherein the method further comprises activating a portion of the metal precursor within the printed object using a pulsed laser to form a plurality of discontinuous metal islands in a predetermined pattern on a surface of the printed object.

[0113] Element 12: wherein the method further comprises performing electroless plating to form one or more conductive traces, wherein the one or more conductive traces interconnect the plurality of discontinuous metal islands.

[0114] Element 13: wherein consolidating a portion of the plurality of thermoplastic particles is performed by selective laser sintering.

[0115] Element 14: wherein the carrier fluid comprises silicone oil.

[0116] Element 15: wherein the thermoplastic particles have an average size in a range of about 1 μm to about 1000 μm in size, or about 10 μm to about 150 μm in size.

[0117] As non-limiting examples, exemplary combinations suitable for A, B, C, and D include, but are not limited to: 1, 1A, 1B, or 1C, and 2; 1, 1A, 1B, or 1C, and 4 or 5; 1, 1A, 1B, or 1C, and 6; 1, 1A, 1B, or 1C, and 7, 7A, 7B, or 7C; 1, 1A, 1B, or 1C, and 10, 10A or 10B; 1, 1A, 1B, or 1C, and 11; 1, 1A, 1B , or 1C, and 11 and 12; 1, 1A, 1B, or 1C, and 13; 1, 1A, 1B, or 1C, and 11 and 13; 1, 1A, 1B, or 1C, and 11-13; 4 or 5, and 6; 4 or 5, and 7, 7A, 7B, or 7C; 4 or 5, and 10, 10A, or 10B; 4 or 5, and 11; 4 or 5, and 11 and 12; 4 or 5, and 13; 4 or 5, and 11 and 13; 4 or 5 , and 11-13; 6 and 7, 7A, 7B or 7C; 6 and 10, 10A, or 10B; 6 and 11; 6, 11 and 12; 6 and 13; 6, 11 and 13; 6 and 11-13; 7, 7A, 7B or 7C, and 8; 7, 7A, 7B or 7C, and 10, 10A or 10B; 7, 7A, 7B or 7C, and 11; 7, 7A, 7B or 7C, and 11 and 12; 7, 7A, 7B or 7C, and and 13; 7, 7A, 7B or 7C, and 11 and 13; 7, 7A, 7B or 7C, and 11-13; 10, 10A or 10B, and 11; 10, 10A or 10B, and 11 and 12; 10, 10A or 10B, and 13; 10, 10A or 10B, and 11 and 13; 10, 10A or 10B, and 11 and 13; 10, 10A or 10B, and 11-13; 11 and 12; 11 and 13; 12 and 13; and 11-13. Any of elements 1-14 may be combined with element 15, or element 15 may be further combined with any of the foregoing combinations of elements 1-14.

[0118] Terms of this Disclosure

[0119] Clause 1. A particulate composition comprising: a plurality of thermoplastic particles comprising a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation.

[0120] Clause 2. The microparticle composition according to clause 1, further comprising:

[0121] A plurality of nanoparticles is disposed on an outer surface of each of the plurality of thermoplastic particles, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof.

[0122] Clause 3. The particulate composition of Clause 2, wherein the plurality of oxide nanoparticles comprises a plurality of silicon dioxide nanoparticles.

[0123] Clause 4. The particulate composition of Clause 1, wherein the metal precursor is thermally stable at a temperature greater than or equal to the melting point or softening temperature of the thermoplastic polymer.

[0124] Clause 5. The microparticle composition according to Clause 1, wherein the metal precursor is capable of being activated by an infrared or near infrared pulsed laser.

[0125] Clause 6. The microparticle composition of Clause 1, wherein the metal precursor is capable of being activated at a wavelength in the range of about 1020 nm to about 1070 nm.

[0126] Clause 7. The microparticle composition of clause 1, wherein the metal precursor comprises at least one material selected from the group consisting of: copper oxide; mixed oxides of copper and a metal selected from the group consisting of: antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium; copper chromium oxide spinel; copper aluminum oxide; copper hydroxide; basic copper phosphate; copper phosphate; copper sulfate; copper thiocyanate; a metal-organic complex comprising a metal selected from the group consisting of: copper, silver, palladium and any combination thereof; and any combination thereof.

[0127] Clause 8. The microparticle composition according to clause 1, further comprising:

[0128] An infrared radiation absorber is blended with the thermoplastic polymer.

[0129] Clause 9. The particulate composition of Clause 8, wherein the infrared radiation absorber comprises a non-stoichiometric metal oxide.

[0130] Clause 10. The microparticle composition of Clause 1, wherein the metal precursor is soluble in the thermoplastic polymer or dispersed in the thermoplastic polymer as microparticles having a particle size ranging from about 10 nm to about 1000 nm.

[0131] Clause 11. The particulate composition of Clause 1, wherein the plurality of thermoplastic particulates comprises from about 1 wt% to about 25 wt% of the metal precursor.

[0132] Clause 12. The microparticle composition according to Clause 1, wherein the thermoplastic microparticles have an average size (D) in the range of about 1 μm to about 1000 μm. 50 ).

[0133] Clause 13. A printed object, the printed object comprising:

[0134] a polymer matrix formed by consolidation of the microparticles and comprising a thermoplastic polymer; and

[0135] A metal precursor is admixed with the polymer matrix, the metal precursor being capable of being activated upon exposure to laser irradiation to form metal islands.

[0136] Clause 14. The printed object according to clause 13, further comprising:

[0137] A plurality of nanoparticles are blended with the polymer matrix, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof.

[0138] Clause 15. The printed object of Clause 14, wherein the plurality of oxide nanoparticles comprises a plurality of silicon dioxide nanoparticles.

[0139] Clause 16. The printed object of Clause 13, wherein the metal precursor is thermally stable at a temperature greater than or equal to the melting point or softening temperature of the thermoplastic polymer.

[0140] Clause 17. The printed object of clause 13, wherein the metal precursor is capable of being activated by an infrared or near infrared pulsed laser.

[0141] Clause 18. The printed object of Clause 13, wherein the metal precursor is capable of being activated at a wavelength in a range of about 1020 nm to about 1070 nm.

[0142] Clause 19. A printed object according to clause 13, wherein the metal precursor comprises at least one material selected from the group consisting of: copper oxide; a mixed oxide of copper and a metal selected from the group consisting of: antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium; copper chromium oxide spinel; copper aluminum oxide; copper hydroxide; basic copper phosphate; copper phosphate; copper sulfate; copper thiocyanate; a metal-organic complex comprising a metal selected from the group consisting of: copper, silver, palladium and any combination thereof; and any combination thereof.

[0143] Clause 20. The printed object according to clause 13, further comprising:

[0144] An infrared radiation absorber is blended with the polymer matrix.

[0145] Clause 21. The printed object of Clause 20, wherein the infrared radiation absorber comprises a non-stoichiometric metal oxide.

[0146] Clause 22. The printed object of Clause 13, wherein the metal precursor is soluble in the polymer matrix or dispersed in the polymer matrix as microparticles, the microparticles having a particle size in the range of about 10 nm to about 1000 nm.

[0147] Clause 23. The printed object of Clause 13, wherein the polymer matrix comprises from about 1 wt % to about 25 wt % of the metal precursor.

[0148] Clause 24. A method comprising:

[0149] depositing a particulate composition in a powder bed, the particulate composition comprising a plurality of thermoplastic particles comprising a thermoplastic polymer and a metal precursor blended with the thermoplastic polymer, the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation; and

[0150] A portion of the plurality of thermoplastic particles in the powder bed is consolidated to form a printed object in which the metal precursor remains substantially unconverted to metal.

[0151] Clause 25. The method of Clause 24, wherein the plurality of thermoplastic particles further comprises a plurality of nanoparticles disposed on an outer surface of each thermoplastic particle in the plurality of thermoplastic particles, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof.

[0152] Clause 26. The method of Clause 25, wherein the plurality of oxide nanoparticles comprises a plurality of silicon dioxide nanoparticles.

[0153] Clause 27. The method of Clause 24, wherein the metal precursor is thermally stable at a temperature greater than or equal to the melting point or softening temperature of the thermoplastic polymer.

[0154] Clause 28. The method according to clause 24, wherein the metal precursor comprises at least one material selected from the group consisting of: copper oxide; mixed oxides of copper and a metal selected from the group consisting of: antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium; copper chromium oxide spinel; copper aluminum oxide; copper hydroxide; basic copper phosphate; copper phosphate; copper sulfate; copper thiocyanate; a metal-organic complex comprising a metal selected from the group consisting of: copper, silver, palladium and any combination thereof; and any combination thereof.

[0155] Clause 29. The method of Clause 24, wherein the plurality of thermoplastic particles further comprises an infrared radiation absorber blended with the thermoplastic polymer.

[0156] Clause 30. The method of Clause 29, wherein the infrared radiation absorber comprises a non-stoichiometric metal oxide.

[0157] Clause 31. The method of Clause 24, wherein the metal precursor is soluble in the thermoplastic polymer or dispersed in the thermoplastic polymer as microparticles having a particle size in the range of about 10 nm to about 1000 nm.

[0158] Clause 32. The method of Clause 24, wherein the plurality of thermoplastic particles comprises from about 1 wt % to about 25 wt % of the metal precursor.

[0159] Clause 33. The method of clause 24, wherein the metal precursor is capable of being activated by an infrared or near infrared pulsed laser.

[0160] Clause 34. The method of Clause 24, wherein the metal precursor is capable of being activated at a wavelength in a range of about 1020 nm to about 1070 nm.

[0161] Clause 35. The method according to clause 24, further comprising:

[0162] A pulsed laser is used to activate a portion of the metal precursor within the printed object to form a plurality of discontinuous metal islands in a predetermined pattern on a surface of the printed object.

[0163] Clause 36. The method according to clause 35, further comprising:

[0164] Electroless plating is performed to form one or more conductive traces interconnecting the plurality of discontinuous metal islands.

[0165] Clause 37. The method of Clause 24, wherein consolidating a portion of the plurality of thermoplastic particles is performed by selective laser sintering.

[0166] Clause 38. The method of Clause 24, wherein the thermoplastic particles have an average size (D) in the range of about 1 μm to about 1000 μm. 50 ).

[0167] Clause 39. A method comprising:

[0168] mixing the thermoplastic polymer with a metal precursor in a carrier fluid at a heated temperature at or above the melting point or softening temperature of the thermoplastic polymer;

[0169] wherein the thermoplastic polymer and the carrier fluid are substantially immiscible at the heating temperature, and the metal precursor is capable of being activated to form metal islands upon exposure to laser irradiation;

[0170] applying sufficient shear at the heated temperature in the presence of the metal precursor to disperse the thermoplastic polymer as liquefied droplets;

[0171] After forming the liquefied droplets, cooling the carrier fluid to at least a temperature to form thermoplastic particles in a solidified state, the thermoplastic particles comprising a thermoplastic polymer and at least a portion of a metal precursor blended with the thermoplastic polymer; and

[0172] The thermoplastic particles are separated from the carrier fluid.

[0173] Clause 40. The method according to clause 39, further comprising:

[0174] combining nanoparticles with the thermoplastic polymer and the metal precursor in the carrier fluid, the plurality of nanoparticles comprising a plurality of oxide nanoparticles, carbon black, or any combination thereof;

[0175] At least a portion of the nanoparticles are disposed on an outer surface of each of the thermoplastic particles.

[0176] Clause 41. The method of Clause 40, wherein the plurality of oxide nanoparticles comprises a plurality of silicon dioxide nanoparticles.

[0177] Clause 42. The method of Clause 39, wherein the metal precursor is thermally stable at a temperature greater than or equal to the melting point or softening temperature.

[0178] Clause 43. The method according to clause 39, wherein the metal precursor comprises at least one material selected from the group consisting of: copper oxide; mixed oxides of copper and a metal selected from the group consisting of: antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium; copper chromium oxide spinel; copper aluminum oxide; copper hydroxide; basic copper phosphate; copper phosphate; copper sulfate; copper thiocyanate; a metal-organic complex comprising a metal selected from the group consisting of: copper, silver, palladium and any combination thereof; and any combination thereof.

[0179] Clause 44. The method according to clause 39, further comprising:

[0180] An infrared radiation absorber is combined in the carrier fluid, the infrared radiation absorber being blended with the thermoplastic polymer in the thermoplastic microparticles.

[0181] Clause 45. The method of Clause 44, wherein the infrared radiation absorber comprises a non-stoichiometric metal oxide.

[0182] Clause 46. The method of Clause 39, wherein the metal precursor is soluble in the thermoplastic polymer or dispersed in the thermoplastic polymer as microparticles having a particle size in the range of about 10 nm to about 1000 nm.

[0183] Clause 47. The method of Clause 39, wherein the thermoplastic particulate comprises from about 1 wt% to about 25 wt% of the metal precursor.

[0184] Clause 48. The method of Clause 39, wherein the metal precursor is activatable by an infrared or near infrared pulsed laser.

[0185] Clause 49. The method of Clause 39, wherein the metal precursor is capable of being activated at a wavelength in the range of about 1020 nm to about 1070 nm.

[0186] Clause 50. The method of Clause 39, wherein the carrier fluid comprises silicone oil.

[0187] Clause 51. The method of Clause 39, wherein the thermoplastic particles have an average size (D) in the range of about 1 μm to about 1000 μm. 50 ).

[0188] In order to facilitate a better understanding of the present disclosure, the following examples of preferred or representative embodiments are given. The following examples should in no way be construed as limiting or defining the scope of the present invention.

[0189] Example

[0190] To a 1 L glass kettle reactor were added 400 g of 10k polydimethylsiloxane (PDMS) oil, 120 g of polyamide 12 containing 5 wt% copper chromite spinel, and 0.4 g of R812S silica with a hydrophobically modified surface (average particle size = 7 nm, and BET surface = 260 + 30 m 2 / g, Evonik). The resulting mixture was heated at 230°C for 30 minutes while stirring at 260 RPM, and then stirred at 1250 rpm for another 40 minutes. After this, heating and stirring were stopped, and the slurry was allowed to cool to room temperature. The resulting microparticles were separated from the silicone oil and washed three times with heptane to remove residual silicone oil. The microparticles were then air-dried in a fume hood to provide microparticles having a size ranging from about 50 microns to about 100 microns.

[0191] All documents described herein are incorporated herein by reference for the purpose of all jurisdictions allowing such practice, including any priority documents and / or testing procedures, as long as they do not conflict with this article. As is apparent from the foregoing general description and specific embodiments, although the form of the present disclosure has been shown and described, various modifications may be made without departing from the spirit and scope of the present disclosure. Therefore, the present disclosure is not intended to be limited thereby. For example, the composition described herein may not contain any component or composition that is not explicitly described or disclosed herein. Any method may lack any step that is not described or disclosed herein. Similarly, the term "comprising" is considered to be synonymous with the term "including". Whenever there is a transition phrase "comprising" before a method, composition, element or element group, it should be understood that we also envision that there is a transition phrase "substantially consisting of...", "consisting of...", "selected from..." or "is" before the narration of the composition, element, multiple elements, or the same composition or element group, and vice versa.

[0192] Unless otherwise indicated, all numbers used in this specification and the related claims expressing the number of components, characteristics (such as molecular weight), reaction conditions, etc. should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the following specification and the attached claims are approximate values, which may vary according to the desired characteristics sought to be obtained by the embodiments of the present invention. At a minimum, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted according to the reported significant digits and by applying conventional rounding methods.

[0193] Whenever a numerical range with a lower limit and an upper limit is disclosed, any number and any included range falling within the range are specifically disclosed. Specifically, each value range disclosed herein (in the form of "about a to about b", or equivalently, "about a to b", or equivalently, "about ab") should be understood to set forth each value and range covered within the wider value range. In addition, the terms in the claims have their ordinary, common meanings unless otherwise explicitly and clearly defined by the patentee. In addition, the indefinite articles "a" or "an" used in the claims are defined herein to mean that there is one or more than one of the elements introduced therein.

[0194] One or more exemplary embodiments are presented herein. For the sake of clarity, all features of physical implementation are not described or shown in this application. It should be understood that in the development of the physical implementation of the present disclosure, many specific decisions must be made to achieve the goal of the developer, such as meeting system-related constraints, business-related constraints, government-related constraints and other constraints, which vary and change over time due to implementation. Although the efforts made by the developer may be time-consuming, such efforts will be a routine task for those of ordinary skill in the art who benefit from the present disclosure.

[0195] Therefore, the present disclosure is well suited to achieve the goals and advantages mentioned, as well as those inherent therein. The specific embodiments disclosed above are merely exemplary, as the present disclosure may be modified and implemented in different but equivalent ways apparent to one of ordinary skill in the art having the benefit of the teachings herein. In addition, no limitations are contemplated on the details of construction or design shown herein, except as described in the following claims. Therefore, it is apparent that the specific exemplary embodiments disclosed above may be altered, combined or modified, and all such variations are considered to be within the scope and spirit of the present disclosure. The embodiments exemplarily disclosed herein may be appropriately implemented in the absence of any element not specifically disclosed herein and / or any optional element disclosed herein.

Claims

1. A microparticle composition, comprising: a plurality of thermoplastic particles, each of the plurality of thermoplastic particles having an outer surface and an interior, the thermoplastic particles comprising a metal precursor blended with a thermoplastic polymer in the interior of the thermoplastic particles, a plurality of nanoparticles, the plurality of nanoparticles disposed on the outer surface of the thermoplastic particles, the plurality of nanoparticles comprising a plurality of silica nanoparticles, carbon black, or any combination thereof, The metal precursor can be activated upon exposure to laser irradiation to form metal islands.

2. The microparticle composition of claim 1, wherein the metal precursor is capable of being activated by an infrared or near infrared pulsed laser.

3. The microparticle composition of claim 1, wherein the metal precursor is capable of being activated at a wavelength in the range of 1020 nm to 1070 nm.

4. The microparticle composition of claim 1, wherein the metal precursor comprises at least one material selected from the group consisting of: copper oxide; mixed oxides of copper and a metal selected from the group consisting of: antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium; copper chromium oxide spinel; copper aluminum oxide; copper hydroxide; basic copper phosphate; copper phosphate; copper sulfate; copper thiocyanate; a metal-organic complex comprising a metal selected from the group consisting of: copper, silver, palladium and any combination thereof; and any combination thereof.

5. The microparticle composition according to claim 1, further comprising: an infrared radiation absorber blended with said thermoplastic polymer; wherein the infrared radiation absorber comprises a non-stoichiometric metal oxide comprising a metal selected from the group consisting of antimony, bismuth, indium, titanium, tin, cesium, zirconium, molybdenum, vanadium, iron, and any combination thereof.

6. The particle composition of claim 1, wherein the metal precursor is dispersed in the thermoplastic polymer as metal precursor particles, and the metal precursor particles have a particle size ranging from 10 nm to 1000 nm.

7. A method comprising: depositing a particulate composition in a powder bed, the particulate composition comprising a plurality of thermoplastic particles, each of the plurality of thermoplastic particles having an outer surface and an interior, the thermoplastic particles comprising a metal precursor blended with a thermoplastic polymer in the interior of the thermoplastic particles, wherein the plurality of thermoplastic particles further comprises a plurality of nanoparticles disposed on the outer surface of the thermoplastic particles, the plurality of nanoparticles comprising a plurality of silica nanoparticles, carbon black, or any combination thereof; the metal precursor being capable of being activated to form metal islands when exposed to laser irradiation; as well as A portion of the plurality of thermoplastic particles in the powder bed is consolidated to form a printed object in which the metal precursor remains substantially unconverted to metal.

8. The method of claim 7, wherein the metal precursor comprises at least one material selected from the group consisting of: copper oxide; mixed oxides of copper and a metal selected from the group consisting of: antimony, aluminum, cesium, cobalt, chromium, magnesium, manganese, nickel, tin, titanium, silver, iron, zinc and zirconium; copper chromium oxide spinel; copper aluminum oxide; copper hydroxide; basic copper phosphate; copper phosphate; copper sulfate; copper thiocyanate; a metal-organic complex comprising a metal selected from the group consisting of: copper, silver, palladium and any combination thereof; and any combination thereof.

9. The method of claim 7, wherein the metal precursor is capable of being activated by an infrared or near infrared pulsed laser.

10. The method according to claim 7, further comprising: A pulsed laser is used to activate a portion of the metal precursor within the printed object to form a plurality of discontinuous metal islands in a predetermined pattern on a surface of the printed object.

11. The method according to claim 10, further comprising: Electroless plating is performed to form one or more conductive traces interconnecting the plurality of discontinuous metal islands.